Prenatal Learning Needs of Multigravid Women at Suntreso Hospital - Bansah, M.A. (University of Ghana, 2003)
The need for effective client education is an important component in midwifery practice. The benefits include a decrease in maternal mortality and morbidity. The purpose of this study was to explore the learning needs of multigravid women. The study was qualitative in nature and an exploratory- descriptive design was adopted. Eighteen multigravida women were selected for the study through a purposive convenience sampling technique. Eight women were interviewed individually and ten engaged in a focus group discussion. Responses were audio taped, transcribed verbatim and content analyzed. Findings indicated that multigravid women had particular learning needs that were not met. Their most important information sources were the prenatal clinic and their mothers. Some of the information from these two sources was in conflict. Responses of the women were sometimes related to misconceptions and inadequate information. Others, generated doubts, anxieties and unsound practices. The women reported that specific topics that the nurses taught, such as preparation for delivery, personal hygiene, nutrition, and aspects of breastfeeding did not reflect their current learning needs. They did however report that topics such as birth control, fetal positions, and sexual activity during pregnancy would be helpful. The women wanted a variety of teaching methods or more interactive teaching styles during teaching periods to address individual and group learning needs. The study provides useful information and strategies from clients’ perspectives that could help to plan, develop and implement prenatal education sessions to meet the felt learning needs of multigravid women and to equip them with relevant information.